2014
DOI: 10.1097/qad.0000000000000272
|View full text |Cite
|
Sign up to set email alerts
|

Association between age at antiretroviral therapy initiation and 24-month immune response in West-African HIV-infected children

Abstract: Objective We describe the association between age at antiretroviral therapy (ART) initiation and 24-month CD4+ cell response in West African HIV-infected children. Methods All HIV-infected children from the IeDEA paediatric West African cohort, initiating ART, with at least two CD4+ cell count measurements, including one at ART initiation (baseline) were included. CD4+ cell gain on ART was estimated using a multivariable linear mixed model adjusted for baseline variables: age, CD4+ cell count, sex, first-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Thus, after ART initiation, immune system disorders can be reversed and associated nutritional problems can be reduced. We report elsewhere in the same population that the initiation of ART at the earliest age before 5 years and before any severe immunodeficiency occurred is needed to optimize the 24-month immune recovery on ART [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, after ART initiation, immune system disorders can be reversed and associated nutritional problems can be reduced. We report elsewhere in the same population that the initiation of ART at the earliest age before 5 years and before any severe immunodeficiency occurred is needed to optimize the 24-month immune recovery on ART [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Consequently, providing a continuum of care for HIV-exposed children remains challenging. Those HIV-infected children who have a chance to access ART are frequently treated late, at an advanced age (median age greater than five years) and at an advanced stage of the disease [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adult studies suggest ART must be started within 12 months of seroconversion to restore immunologic health [ 44 ] and early ART initiation might contribute to more rapid and robust CD4:CD8 ratio normalization [ 29 ]. In children, one report demonstrated that starting ART before 5 years of age results in stronger CD4 T cell gains but not normalization within 24 months of treatment [ 34 ]. A statistical model developed to estimate long-term CD4 recovery, demonstrated that ART should be initiated when CD4-for-age is high, even if there is a low risk of immediate disease progression to maximize CD4 reconstitution in children older than 10 years [ 45 ].…”
Section: Discussionmentioning
confidence: 99%